2021
DOI: 10.21037/atm-21-1340
|View full text |Cite
|
Sign up to set email alerts
|

Ki67 and progesterone receptor status predicts sensitivity to palbociclib: a real-world study

Abstract: Background: Palbociclib combined with endocrine therapy has been approved as a front-line treatment for hormone receptor positive (HR+), human epidermal growth factor receptor 2 negative (HER2−) advanced breast cancer (ABC). A key challenge remains to uncover biomarkers to identify those patients who may benefit from palbociclib treatment.Methods: We retrospectively analyzed the values of Ki67 and progesterone receptor (PR) as detected by immunohistochemistry in 81 ABC patients with palbociclib and hormone the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 47 publications
4
15
0
Order By: Relevance
“…Previous research has suggested PgR and Ki-67 state to affect the efficacy of palbociclib ( 33 ). Our study also suggested that Ki-67 expression, but not PgR status, was related to PFS following a palbociclib-containing treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested PgR and Ki-67 state to affect the efficacy of palbociclib ( 33 ). Our study also suggested that Ki-67 expression, but not PgR status, was related to PFS following a palbociclib-containing treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Rugo et al [5] found that the survival benefit of CDK4/6i was not associated with Ki67 expression in metastatic BC. In contrast, the recent study by Shao et al [4] showed that patients with Ki67 <14% and PR ≥20% had significantly longer PFS than those with Ki67 ≥14% and PR <20%. Hence, it is unclear from these previous studies whether Ki67 expression and PR expression can predict palbociclib efficacy.…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, in the monarchE trial the authors found that high Ki67 levels (Ki67 ≥20%) showed benefit of abemaciclib and ET in the adjuvant setting for ER-positive, HER2- negative early-stage BC with high-risk features [17]. Although much effort has been exerted in the adjuvant setting, the prognostic benefit of Ki67 and PR expression to predict palbociclib efficacy in the metastatic setting is still not clear despite discussion in the literature [1, 4, 5]. Palleschi et al [1] showed that Ki67 can predict CDK4/6i + ET efficacy in metastatic BC but PR expression failed to show any benefit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ki67 is an important indicator of the cell proliferation rate for evaluating tumor malignancy and has been used to predict prognoses for various malignant tumor types (11). Recent studies using 30% as the cut-off Ki67 value for stratified analysis have likewise determined that a high Ki67 score (30%) is a potential prognostic marker and predictor of neoadjuvant or adjuvant chemotherapy efficacy in breast cancer and other malignant diseases (12)(13)(14)(15)(16). More specifically, a series of studies have indicated that the Ki67 level appears to be a strong and robust predictor of metastasis as well as an indicator of poor prognosis in melanoma (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%